Fungsi Tuas Stamen dalam Penyerbukan dan Potensi Bunga Salvia sebagai Tanaman Hias di Kebun Raya Cibodas - , Sudarmono; , Destri (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2013)
ABSTRACTStaminodes or sterile stamen of S. splendens Wied Sellow ex-Neuw and S. ianthina Otto & Dietr. ( Lamiaceae) significantly affected the pollination process of the species. Sterile stamen is directly and closely related to insects or pollinator and in directly related in the process of evolution of S. splendens and S. ianthina. Following the assumption that the evolutionary process on members of Lamiaceae based on the structure of the flowers, the sterile stamens on the flowers S. splendens and S. ianthina plays an important role in attaching the pollen grains on the body of pollinators. Pollinator interactions to a floweris significant on the pollination system. Sterile stamens was the lever mechanism tested in field research , experimentalbiomechanics and pollination simulation, and the result was seed production lower of S. splendens (55% ± 6.4%) and S. ianthina (25% ± 10.6%) when without staminodes than control of S. splendens (70% ± 4.2%) and S. ianthina (35% ± 9.2%). The beauty of the flowers that are commonly found in members of theLamiaceae is the potential of S. splendens and S. ianthina.Key words: Cibodas Botanic Garden, pollinators, S. ianthina , S. splendens, stamens.ABSTRAKStaminoda atau tangkai benang sari (stamen) steril pada S. splendens Wied Sellow ex- Neuwdan S. ianthina Otto & Dietr. (Lamiaceae) berpengaruh nyata pada proses penyerbukannya. Stamen steril secara langsung berkaitan erat dengan serangga atau penyerbuk dan secara tidak langsung terhadap proses evolusi pada S. splendens dan S. ianthina. Diasumsikan bahwa proses evolusi pada anggota Lamiaceaedidasarkan pada struktur bunga, stamen steril pada bunga S. splendens dan S. ianthina yang mana memainkan peranan penting pada penempelan butir sari pada tubuh penyerbuk. Penyerbuk berinteraksi pada suatu bunga secara nyata dalam sistem penyerbukan. Stamen steril diuji mekanisme tuasnya pada percobaan lapangan, percobaan biomekanik dan simulasi penyerbukan, dan hasilnya adalah produksi biji rendah padaS. splendens ( 55% ± 6. 4%) dan S. ianthina 25% ± 10. 6%) ketika tanpa staminoda daripada perlakuan kontrol pada S. splendens (70% ± 4. 2% dan S. ianthina 35% ± 9. 2%). Keindahan bunga yang umum ditemukan pada anggota Lamiaceae merupakan potensi pada S. splendens dan S. ianthina .Kata kunci: Kebun Raya Cibodas, penyerbuk, S. ianthina, S. splendens, stamen